2016
DOI: 10.1103/physreve.93.052115
|View full text |Cite
|
Sign up to set email alerts
|

First-order phase transition in a model of self-propelled particles with variable angular range of interaction

Abstract: We have carried out a Monte Carlo simulation of a modified version of Vicsek model for the motion of self-propelled particles in two dimensions. In this model the neighborhood of interaction of a particle is a sector of the circle with the particle at the center (rather than the whole circle as in the original Vicsek model). The sector is centered along the direction of the velocity of the particle, and the half-opening angle of this sector is called the 'view-angle'. We vary the view-angle over its entire ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
1
20
1
Order By: Relevance
“…In other words, if the magnitude of noise is not too large, there is a sharp phase transition as the sensing angle increases. This sharp phase transition is also reported for two-dimensional model in [18]. Moreover, the phase transition as the sensing angle increases in the presence of passive sensing (figure 2) appears more gradual in comparison to the phase transition when particles only use active sensing in figure 3.…”
Section: Simulationssupporting
confidence: 78%
See 1 more Smart Citation
“…In other words, if the magnitude of noise is not too large, there is a sharp phase transition as the sensing angle increases. This sharp phase transition is also reported for two-dimensional model in [18]. Moreover, the phase transition as the sensing angle increases in the presence of passive sensing (figure 2) appears more gradual in comparison to the phase transition when particles only use active sensing in figure 3.…”
Section: Simulationssupporting
confidence: 78%
“…Therefore, no phase transition with respect to noise happens for the case with sensing angle is less than π 2 . Durve and Sayeed use the same model to study polarization as sensing angle is varied [18]. The authors find that the phase transition is of the first order when sensing angle is varied, while it is of the second order when the radius of the circular neighborhood around the particle is varied.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of non-reciprocity has been incidentally encountered (but not addressed specifically) in a few studies that explore the role of limited vision-cone of active, interacting agents in a flock. Angular restriction on the reorientation of an individual agent within a flock alone can facilitate ordering [55] and can also affect the thermodynamic character of the order-disorder transition occuring within the flocks [56]. It was also observed that angular restriction on interaction neighborhood in Vicsek model can reduce time required to reach ordered state from a disordered state [57].…”
Section: Introductionmentioning
confidence: 99%
“…It can even be found in variants of simple flocking models such as the Vicsek model, where local alignment of constantspeed particles competes with noise [22][23][24]. In [15][16][17][18][19], the introduction of a limited angle of vision was shown to have an influence on the shape of cohesive moving groups, on the degree of ordering, etc. Asymmetric interactions are also present in 'metric-free' models introduced in the context of bird flocks [11][12][13][14].…”
mentioning
confidence: 99%